A database on the passage and enactment of recent state minimum wage increases - Michael R. Strain; Jeffrey Clemens; Duncan Hobbs (American Enterprise Institute (AEI), 2018)
This paper presents a data set that tracks effective minimum wage rates across the US states, including the District of Columbia, from January 1, 2011, to January 1, 2018.
Keywords: A; 330; Minimum Wage